Non-Hormonal Therapy for Endometriosis Based on Angiogenesis, Oxidative Stress and Inflammation - Khadijeh Sanamiri; Soodeh Mahdian; Ashraf Moini; Maryam Shahhoseini (International Journal of Fertility and Sterility, 2024)
Endometriosis is a common gynecological disease that occurs in between 6 and 10% of women who are at reproductivematurity. The presence of endometrial tissue outside the uterine cavity is the defining characteristic of thisdisease. Although the etiology of endometriosis remains controversial, there is a general consensus that multiple biologicalprocesses such as angiogenesis and vasculogenesis, oxidative stress, and inflammation contribute to its complexpathophysiology. Patients’ expectations and priorities influence the treatment plan that is selected. For instance,therapy with hormone medications is inappropriate for endometriosis patients who wish to become pregnant sincethese medications interfere with ovulation. On the other hand, considering that the current endometriosis treatmentsare associated with recurrence of pain and disease despite the treatment of the disease and have many side effects,the design and application of non-hormonal drugs in this field is very necessary. Therefore, in this article, we triedto have an overview on non-hormonal treatments by considering angiogenesis, oxidative stress, and inflammation asimportant biological processes involved in endometriosis.